Capital and consumption led growth: case study in Malaysia, Singapore, Japan and Zimbabwe / Mohd Azlan Abdul Majid, Mariam Setapa and Noorita Mohammad - Abdul Majid, Mohd Azlan; Setapa, Mariam; Mohammad, Noorita (Research Management Institute (RMI), 2010)
The purpose of this paper is to examine the impact of capital and consumption on the economic growth especially in Malaysia and compare to other countries like Japan, Singapore and Zimbabwe. Our study will be using a few methods such as Unit Root Test (URT); i. Augmented Dickey-Fuller Method (ADF), ii. Phillip-Perron Test (PP) and iii. Kwiatkowski-Phillip-Schmidt-Shin, Johnson Cointegration Test (JCT), followed by Vector Error Correction Model (UECM) and lastly by using Granger Causality Test (GCT). This paper finds that it's support capital-led growth hypotheses, but for consumption result differs for each tier development which is Malaysia & Singapore are support; Zimbabwe and Japan are partial support. This study is perhaps one of the first to address capital and consumption led growth using the new model / extended model to boost the economic growth of Malaysia. Keywords: capital-led growth; consumption-led growth; unit root; cointegration; granger causality